2010
DOI: 10.1186/1471-230x-10-2
|View full text |Cite
|
Sign up to set email alerts
|

The clinical presentations of ectopic biliary drainage into duodenal bulbus and stomach with a thorough review of the current literature

Abstract: BackgroundEctopic biliary drainage is a rare congenital anomaly on which we have scarce data in the current literature.MethodsThe data were collected from the records of 400 endoscopic retrograde cholangio-pancreatography (ERCP). In this report, we present 10 cases (male/female: 9/1, mean age 54 years, range 38-74) with ectopic biliary openings into the duodenum and/or stomach diagnosed by endoscopic retrograde cholangio-pancreatography (ERCP).ResultsIn our series, the frequency of ectopic biliary drainage is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 19 publications
1
40
1
Order By: Relevance
“…Some previous reports described the presence of the major papilla in the second portion of the duodenum (1, 6, 7). In other reports, the pancreatic duct was visualized in fewer than half of the total cases (2)(3)(4)(5)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), which suggests the possibility of another orifice joining with the pancreatic duct. Moreover, from the viewpoint of the embryonic process, the presence of the major papilla is consistent with Boyden's theory (30), as described above.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…Some previous reports described the presence of the major papilla in the second portion of the duodenum (1, 6, 7). In other reports, the pancreatic duct was visualized in fewer than half of the total cases (2)(3)(4)(5)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), which suggests the possibility of another orifice joining with the pancreatic duct. Moreover, from the viewpoint of the embryonic process, the presence of the major papilla is consistent with Boyden's theory (30), as described above.…”
Section: Discussionmentioning
confidence: 75%
“…Previous reports have suggested that the incidence of PD in autopsy cases is about 9% (21,22). To our knowledge, this is the first report of an ectopic opening of the CBD into the duodenal bulb accompanied by choledochocele and PD (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Choledochocele concomitant with PD is also rare, with only three case reports having been published (25)(26)(27); therefore, our case is extremely rare.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…So in difficult ERCP where the papilla cannot be found in its usual location ectopic biliary drainage and abnormal situation of papilla must be considered and searched. The frequency of ectopic biliary drainage by ERCP is 2% (10 out of 400 ERCP) 8 .…”
Section: Discussionmentioning
confidence: 99%